2009
DOI: 10.1088/1126-6708/2009/05/021
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamics of holographic superconductors

Abstract: We study the poles of the retarded Green functions of a holographic superconductor. The model shows a second order phase transition where a charged scalar operator condenses and a U (1) symmetry is spontaneously broken. The poles of the holographic Green functions are the quasinormal modes in an AdS black hole background. We study the spectrum of quasinormal frequencies in the broken phase, where we establish the appearance of a massless or hydrodynamic mode at the critical temperature as expected for a second… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

17
225
0
9

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(251 citation statements)
references
References 45 publications
17
225
0
9
Order By: Relevance
“…The AdS/CFT duality is a powerful tool for investigating strongly coupled gauge theories, the application might offer new insight into the study of strongly interacting condensed matter systems where the perturbational methods are no longer available. Therefore, much attention has been given to the studies of the AdS/CFT duality to condensed matter physics and in particular to superconductivity recently [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. In these studies most of the holographically dual descriptions for a superconductor are based on a model that a simple Einstein-Maxwell theory coupled to a charged scalar.…”
Section: Introductionmentioning
confidence: 99%
“…The AdS/CFT duality is a powerful tool for investigating strongly coupled gauge theories, the application might offer new insight into the study of strongly interacting condensed matter systems where the perturbational methods are no longer available. Therefore, much attention has been given to the studies of the AdS/CFT duality to condensed matter physics and in particular to superconductivity recently [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. In these studies most of the holographically dual descriptions for a superconductor are based on a model that a simple Einstein-Maxwell theory coupled to a charged scalar.…”
Section: Introductionmentioning
confidence: 99%
“…In the immediate future, one might also construct vortices and compare them with the dark solitons [21]. In a closely related work, the hydrodynamic properties of this system was studied [22]. It would be important to examine the relation between that study and ours.…”
mentioning
confidence: 97%
“…This system of equations, with the symmetry structure (5.21), is identical to that studied in [46][47][48], where it was found that, in the hydrodynamic limit ω, κ 1, the poles of the lie on:…”
Section: Jhep01(2014)054mentioning
confidence: 70%